Contribuição ao desenvolvimento de metodologia para detecção de desintegrina recombinante produzida em cultivos de células CHO-K1 - Silva, Gracinda Marina Castelo da (Universidade Federal de São Carlos, 2004)
Disintegrins are proteins present in the poison of serpents that have been calling the pharmaceutical industry attention due to their capacity to prevent the progression of cancerous cells. A receiving key-protein called integrin addresses the formation of new blood vessels instructing the tumor cells to increase and spread. The disintegrin acts as an inhibitor that blocks this interaction. In order to produce substantial amounts of disintegrin in industrial scale, its expression in CHO-K1 cells was carried out by cloning the characteristic DNA extracted from the poison producing glands of the serpent Agkistrodon contortrix laticinctus. Usually CHO-K1 cells are cultivated in medium containing bovine fetal serum. However, its presence in the cultivation medium hinders the stages of detection, extraction and purification of the protein of interest. The objective of this work was to study the CHOZMD cell growth and the desintegrin production in serum free medium, as well as to develope a methodology for the detection and quantification of the disintegrin present in the medium. The cultivations were carried in culture bottles of 25cm2, 75cm2 and 150cm2 and later in spinner flask with a volume of 500mL, incubated with an amount of CO2 controlled in 10% v/v, pH between 7.0 to 7.4, a temperature of 37 °C, under agitation conditions. The cells were cultivated in the presence of the microcarrrier Pronectin F which enables the attainment of high cell concentration. The culture media DMEM and CHO-S-SFM II were used in the cultivations by means of a gradual adaptation process for a serum free medium, through the reduction of DMEM+serum proportion at each change, until that it was totally replaced by the serum free medium. The cells were maintained in 100% serum free medium during 6h with the withdrawal of 250 ml after 3 h and of the remaining volume after 6h of cultivation. For the detection of the disintegrin, the samples were initially filtered in Milipore filter, then concentrated in ultra filter Amicon and finally centrifuged in membranes Centriprep and Centricon. The disintegrin, protein of ~70kDa, present in the treated samples was detected using Bio Dot equipment with nitrocelulose membrane incubated with specific antibodies. The samples were applied in ion exchange column and the fractions obtained applied in nitrocelulose membrane. In the cultivations carried out in serum free medium with the microcarrier Pronectin F a maximum cell concentration of 1.74.106 cel.ml-1 was reached, which is slightly inferior to the value reached in the cultivations in medium containing serum (2.7.106 cel.mL-1). However, concerning product formation, the immunodetecion results revealed the presence of the disintegrin in the cultivations carried out with serum free medium. Cultivations carried out in spinner flask, with a volume of 200mL and using microcarrier Citodex 1 and medium supplemented with 1% hemolymph (v/v) presented maximum cell concentration of 2.6.106 cel.mL-1. The detection method developed was effective in the identification of the target protein in the samples from the cultivation medium containing hemolymph. Preliminary tests demonstrated loss of protein might be related to gradual degradation in cultivation medium or retention in ion exchange column.
Keywords: Biotecnologia; Células CHO-K1; Proteína recombinante; Engenharia bioquímica; ENGENHARIAS::ENGENHARIA QUIMICA